2008
DOI: 10.2522/ptj.20070314
|View full text |Cite
|
Sign up to set email alerts
|

Reference Curves for the Gross Motor Function Measure: Percentiles for Clinical Description and Tracking Over Time Among Children With Cerebral Palsy

Abstract: The reference percentiles extend the clinical utility of the GMFM-66 and GMFCS by providing for appropriate normative interpretation of GMFM-66 scores within GMFCS levels. When interpreting change in percentiles over time, therapists must carefully consider the large variability in change that is typical among children with CP. The use of percentiles should be supplemented by interpretation of the raw scores to understand change in function as well as relative standing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
225
3
27

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 220 publications
(269 citation statements)
references
References 23 publications
14
225
3
27
Order By: Relevance
“…Cerebral Palsy (CP) is the most prevalent diagnosis for children with significant motor impairments who are followed by physical and occupational therapists [1]. This diagnosis results in lifelong progressive deforming secondary sequellae, most likely as a direct result of immobility.…”
Section: Introductionmentioning
confidence: 99%
“…Cerebral Palsy (CP) is the most prevalent diagnosis for children with significant motor impairments who are followed by physical and occupational therapists [1]. This diagnosis results in lifelong progressive deforming secondary sequellae, most likely as a direct result of immobility.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies of representative groups of children with CP, with mainly a level III deficit have shown maximal improvement of motor functions up to the age of 10 years with standard rehabilitation including mechanotherapy; afterwards motor skills did not increase and in some cases even decreased [13]. Using the GMFM-88 scale, we have shown that improvement occurred in less than 50% of the cases in the control group, while in the experimental group 81% of the subjects showed improved motor skills.…”
Section: Discussionmentioning
confidence: 85%
“…In the first module, smaller and younger children had better outcomes for motor improvements. The same explanation could be used when statistical differences were found between pre-and posttest in the modules, considering majority of sample is younger than 7 years and that previous studies identified stability of motor performance from this age (Hanna, Bartlett, Rivard, & Russell, 2008;Hanna et al, 2009).…”
Section: Discussionmentioning
confidence: 99%